Injuries, Suffered by Nurses, Changing Patients’ Position - Petravičienė, Zita; Bartašiūnienė, Vida (Slauga. Mokslas ir praktika, 2021)
As recently as 20 years ago, the International Labor Organization has drawn the attention to the nurses’ working conditions, nursing and health. Nursing is one of the professions, mostly exposed to the risk of experiencing back injuries. One of the main precautions to prevent nurses’ back injuries is the use of technical aids and the work environment provision with ergonomic means. There must be a lot and diverse devices in the workplace available for nurses to protect them from injuries [1]. The European Agency for Safety and Health at Work identifies several groups of risk factors that affect the health of nurses. They are work-related risks (monotonous movements, use of physical force, an uncomfortable body position), patient-related risks (a heavy patient, immobility, etc.), environment-related risks (slippery work surfaces, limited area, etc.), and other risks (lack of knowledge, inappropriate clothing and footwear, etc.) [2]. The aim of the research was to analyze the injuries experienced by nurses in changing the situation of patients. A quantitative survey was conducted, providing the questionnaires; its participants were nurses, working in Utena City health care institutions. The nurses usually experience various types of sprains of back, lumbar and shoulder girdle muscles. Injuries, suffered by nurses, are related to the lack of additional facilitators and knowledge on how to lift a patient in a correct manner.